Aristotle in Hollywood : the anatomy of successful storytelling - Hiltunen, Ari (Studies in scriptwriting., 2002)
Throughout the centuries Aristotle's Poetics remained something of a mystery. What was the great philosopher trying to say about the nature of drama and storytelling? What did he mean by pity, fear and catharsis? In this book, Ari Hiltunen explains the mystery of the 'proper pleasure', which, according to Aristotle, is the goal of drama and can be brought about by using certain storytelling strategies. Hiltunen develops Aristotle's thesis to demonstrate how the world's best-loved fairy tales, Shakespeare's success, and empirical studies on the enjoyment of drama and brain physiology, all give support to the idea of a universal 'proper pleasure' through storytelling. Examining the key concepts and logic of Poetics, Hiltunen offers a unique insight to anyone who wants to know the secret of successful storytelling, both in the past and in today's multi-billion dollar entertainment industry.